2010
DOI: 10.1016/j.jpeds.2009.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Low Aerobic Fitness and Obesity Are Associated with Lower Standardized Test Scores in Children

Abstract: Objective-To investigate whether aerobic fitness and obesity in school children are associated with standardized test performance.Study design-1,989 ethnically diverse fifth, seventh and ninth graders attending California schools comprised the sample. Aerobic fitness was determined by a one-mile run/walk test; BMI was obtained from state-mandated measurements. California standardized test scores were obtained from the school district.Results-Students whose mile run/walk times exceeded California Fitnessgram st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
108
4
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 21 publications
13
108
4
6
Order By: Relevance
“…It shows that children with low motor function score have lower scores in writing test. This was consistent with some previous studies reported that academic performance would affect students' motor function [9,[24][25][26]. However, extracurricular activities, like bimanual coordination movement are necessary to help weak students because more opportunities for interaction may lead to an increase in productive academic achievements.…”
Section: Discussionsupporting
confidence: 92%
“…It shows that children with low motor function score have lower scores in writing test. This was consistent with some previous studies reported that academic performance would affect students' motor function [9,[24][25][26]. However, extracurricular activities, like bimanual coordination movement are necessary to help weak students because more opportunities for interaction may lead to an increase in productive academic achievements.…”
Section: Discussionsupporting
confidence: 92%
“…34 BMI and skinfold thickness were used as indicators of body fat because of 1) the results on the association between positive health and obesity in children and adolescents is inconclusive, [37][38][39][40] which might be due to the fact that the adiposity indicator used varies among studies; 2) to make our data comparable with other studies using mainly BMI; and 3) because it could be argue that BMI is not a valid indicator of body fat in children and adolescents, 41 and it could be also argue that skinfold thickness is not a valid indicator of body fat in obese children and adolescents (due to the fact that the measurement error increases in these individuals). 41 …”
Section: Methodsmentioning
confidence: 99%
“…Regular physical activity improves cognitive function, induces brain changes, and improves mood in children, in addition to improving their aerobic fitness [3][4][5][6][7][8]. Greater aerobic fitness and physical activity are associated cross sectionally with increased grade point averages and standardized test scores [9][10][11]. There is some evidence that increasing physical activity can improve student grade point averages and standardized test scores [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%